Induction of cytokine granulocyte-macrophage colony-stimulating factor and chemokine macrophage inflammatory protein 2 mRNAs in macrophages by Legionella pneumophila or Salmonella typhimurium attachment requires different ligand-receptor systems. - Yamamoto, Y (1996)
The attachment of bacteria to macrophages is mediated by different ligands and receptors and induces various intracellular molecular responses. In the present study, induction of cytokines and chemokines, especially granulocyte-macrophage colony-stimulating factor (GM-CSF) and macrophage inflammatory protein 2 (MIP-2), was examined, following bacterial attachment, with regard to the ligand-receptor systems involved. Attachment of Legionella pneumophila or Salmonella typhimurium to cultured mouse peritoneal macrophages increased the steady-state levels of cellular mRNAs for the cytokines interleukin 1beta (IL-1beta), IL-6, and GM-CSF as well as the chemokines MIP-1beta, MIP-2, and KC. However, when macrophages were treated with alpha-methyl-D-mannoside (alphaMM), a competitor of glycopeptide ligands, induction of cytokine mRNAs was inhibited, but the levels of chemokine mRNAs were not. Pretreatment of the bacteria with fresh mouse serum enhanced the level of GM-CSF mRNA but not the level of MIP-2 mRNA. In addition, serum treatment reduced the inhibitory effect of alphaMM on GM-CSF mRNA. These results indicate that bacterial attachment increases the steady-state levels of the cytokine and chemokine mRNAs tested by at least two distinct receptor-ligand systems, namely, one linked to cytokine induction and involving mannose or other sugar residues and the other linked to chemokine induction and relatively alphaMM insensitive. Furthermore, opsonization with serum engages other pathways in the cytokine response which are relatively independent of the alphaMM-sensitive system. Regarding bacterial surface ligands involved in cytokine mRNA induction, evidence is presented that the flagellum may be important in stimulating cytokine GM-CSF message but not chemokine MIP-2 message. Analysis of cytokine GM-CSF and chemokine MIP-2 signaling pathways with protein kinase inhibitors revealed the involvement of calmodulin and myosin light-chain kinase in GM-CSF but not MIP-2 mRNA induction, adding further evidence that several distinct receptor systems are engaged during the process of bacterial attachment and induction of cytokines and chemokines, such as GM-CSF and MIP-2, respectively.